Хорольський район Полтавщини у 1942 р. (за щоденником Дмитра Захаровича Браженка) - Еткіна, І. (Сiверянський лiтопис, 2015)
У даній публікації вперше оприлюднений черговий уривок щоденника сільського вчителя Д.З. Браженка часів Другої світової війни. У передмові матеріали даного уривка співставлено з іншими джерелами та даними наукової літератури, увага приділяється проблемам економічного визиску окупантами українського села, примусового вивезення жителів сіл на роботи до Німеччини, становища сільських шкіл під окупацією. В данной публикации впервые обнародован следующий отрывок дневника сельского учителя Д.З. Браженка времен Второй мировой войны. В предисловии материалы этого отрывка сопоставлены с другими источниками и данными научной литературы, обращается внимание на проблемы экономической эксплуатации оккупантами украинского села, принудительного вывоза жителей сел на работы в Германию, состояния сельских школ во время оккупации. The article first brings into the light the next fragment of a rural teacher’s diary Brazhenko D. Z. World War II period. The chronological limits of the passage – August, 22 – December, 29, 1942 were determined to the removal of his family from Chernigiv region to Khorol district in Poltava region and the end of the calendar year. This passage gives a unique opportunity for the historian to compare the occupation regimen in Chernigiv region, in the area of military control and Poltava, Reichskommissariat «Ukraine». The author of the diary makes the conclusions that the situation in Poltava region was much calmer. In this passage there are no events which related with the partisan movement, response of German reprisals against the local population, the feeling of anxiety of the peasants. And this feeling fills the diary which was written in Chernigiv region. However, the expected facilitate the family Brazhenko didn’t feel due to the worse economic situation in Poltava region. The occupation’s control above the village was total. Peasants were imposed with huge natural taxes such as milk, eggs, meat, etc. Besides, peasants had to pay huge cash taxes. Information about the merciless exploitation of the peasantry confirmed in modern scientific literature. The Germans promised to divide the collective farms’ land between the peasantry, but because of the huge taxes the peasants didn’t believe in their outreach. At the same time, the occupation authorities carried out a monetary reform and printed new Ukrainian money instead of Soviet rubles. This reform was held in order to confiscate money and it was extremely unprofitable to people. The author of the diary became a head of the school in the village Verguny in Khorol district. But his salary was scanty and the family with two children lived half-starving. Brazhenko Dmutro noticed that the occupation authorities in Chernigiv region had a better attitude to rural school than in Poltava: gave money for the repair, taught the German language and there was more order. Here books and even globes were taken to review and censorship them. Brazhenko Dmutro gets a task to agitate the local people to go to work in Germany. He treated this work as forced as he saw that removal was forced and sympathized with the villagers. The author does not hide the problems of dipsomania in Ukrainian villages during the occupation, which was because the fear, grief and poverty. In November 1942 with Germans’ permission, the villagers celebrated the harvest festival. This passage allows the historian to see the experience of survival of the person and his family in the crucial military situation and to show aii its complexity.